2016
DOI: 10.1016/j.vaccine.2016.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards antenatal vaccination, Group B streptococcus and participation in clinical trials: Insights from focus groups and interviews of parents and healthcare professionals

Abstract: In order for a future GBS vaccine to be acceptable to both pregnant women and the healthcare professionals advising them, a major awareness campaign would be required with significant focus on convincing and training maternity professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Qualitative findings from focus group discussions and in-depth interviews were generally consistent with the quantitative results: an unambiguous recommendation from an HCP to vaccinate against seasonal influenza or pertussis is key to pregnant women being vaccinated [ 58 66 , 68 , 72 , 73 , 76 , 77 ]. It is difficult to draw conclusions about which specific HCP (e.g.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Qualitative findings from focus group discussions and in-depth interviews were generally consistent with the quantitative results: an unambiguous recommendation from an HCP to vaccinate against seasonal influenza or pertussis is key to pregnant women being vaccinated [ 58 66 , 68 , 72 , 73 , 76 , 77 ]. It is difficult to draw conclusions about which specific HCP (e.g.…”
Section: Discussionsupporting
confidence: 65%
“…Additionally, several studies reported preferences for natural immunity or a healthy lifestyle during pregnancy as reasons to decline vaccinations [ 61 , 62 , 66 , 68 , 76 ]. Maternal vaccination decision-making was also associated with several emotions and sentiments including fear (13 studies) [ 61 , 62 , 64 , 67 73 , 75 77 ], worry or anxiety (8 studies) [ 56 , 58 , 61 , 63 , 67 , 70 , 72 , 77 ], responsibility for pregnancy outcomes and culpability if something goes wrong (5 studies) [ 61 , 68 , 71 , 73 , 76 ], and uncertainty about risks associated with vaccination decisions (3 studies) [ 63 , 75 , 76 ]. Pregnant women feared the unknown [ 68 , 70 72 ] the disease (particularly for pandemic influenza) [ 62 , 68 , 70 , 73 ], vaccine harm or side-effects [ 61 , 64 , 67 , 69 , 70 , 75 , 76 ], vaccine safety [ 64 , 73 ], and pain [ 52 , 61 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouragingly, almost a quarter of pregnant women would consider taking part in a hypothetical GBS clinical trial and healthcare professionals were also supportive in that they would be willing to provide significant practical help to the study teams. The involvement of the patient's own clinician is particularly important in optimizing participation , although our previous qualitative work has suggested that some maternity professionals may be very ambivalent about clinical vaccine trials . It is reassuring that these were not the views of this more representative sample of UK maternity professionals and suggests that recruiting local staff to be part of the study team could be key to success.…”
Section: Discussionmentioning
confidence: 88%
“…The questionnaires were developed after reviewing the literature, using data collected from an online survey of over 1000 women of child‐bearing age , and in‐depth qualitative work with pregnant women, parents with experience of GBS and maternity professionals . Prior to the national survey, the questionnaires were piloted among the interview and focus group participants and adapted based on their feedback.…”
Section: Methodsmentioning
confidence: 99%